Factors Associated With Regorafenib Adherence With Metastatic Colorectal Cancer - Kawakami, Kazuyoshi (Patient Prefer Adherence, 2019)
INTRODUCTION: Regorafenib is an oral multikinase inhibitor for the treatment of metastatic colorectal cancer (mCRC). The clinical factors that may affect adherence to regorafenib remain unclear. The aim of this study was to evaluate adherence to regorafenib with mCRC and to identify factors that might affect adherence to regorafenib. METHODS: A total of 108 consecutively enrolled Japanese patients with mCRC received regorafenib. Adherence was measured by pharmacists using pill counts and a self-reported treatment diary for patients at a pharmaceutical outpatient clinic. The median relative dose intensities of regorafenib and the factors adversely affecting adherence were retrospectively surveyed. Logistic regression analysis was then performed using patient socio-demographic factors and clinical factors. RESULTS: A total of 96 patients were included in the analysis. The median adherence rate was 61.7% in the first cycle. The median relative dose intensity was 57.1%. The most common reason for non-adherence was a hand-foot-skin reaction (35.6%). On multivariate analysis, increased non-adherence to regorafenib was significantly associated with sex (female) [odds ratio (OR) = 4.36; 95% confidence interval (CI): 1.43–13.22, p = 0.01]. DISCUSSION: Hand-foot-skin reactions and female sex were associated with lower adherence to regorafenib. Since these factors could be associated with lower adherence to regorafenib, it would be useful to consider these factors when assessing adherence.